The clinical effects of implantation of Acrysof IQ Restor multifocal Toric lens - XiaoCHEN; FuweiGOU; MaoshengCHEN (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Objective: To evaluate the early clinical effects and safety of phacoemulsification with implantation of Acrysof IQ Restor Toric lens, and investigate the vision quantity of the patients with implantation of Acrysof IQ Restor Toric lens. Methods: We retrospectively analyzed 18 cases (23 eyes) of corneal astigmatism ≥1.0 diopter treated by phacoemulsification with implantation of Acrysof IQ Restor Toric lens. Patients were followed up for 3 months. The patients were observed with uncorrected distance visual acuity (UCVA), best corrected distance visual acuity (BCVA), uncorrected near visual acuity (UNVA), astigmatism before and after surgery, spherical equivalent refraction, and rational stability of the IOL. Results: At 3 months after the surgery, UCVA was 0.89±0.21, BCVA was 0.95±0.38, spherical equivalent refraction was −0.5~+0.25 D, UNVA was 0.82±0.19. Overall astigmatism was (0.38±0.15) diopter, less than the astigmatism before surgery (1.79±0.43) Diopter (P Conclusion: Acrysof IQ Restor multifocal Toric lens provides excellent overall vision and visual quality for cataract patients, corrects corneal astigmatism with rotational stability, increases the rate of satisfactory and removal of lens, and also has good predictability and rotary stability.